Morphological observation of puparia of Chrysomya nigripes (Diptera: Calliphoridae) from human corpse - Sukontason K.L. (2014)
This article presents Chrysomya nigripes Aubertin as a blow fly species of forensic importance in Thailand, and morphological observation of fly puparia using scanning electron microscopy (SEM). Morphologically, we focused on the characteristics of puparia used to accurately identify fly species. Numerous puparia of C. nigripes were found aggregated, adhering side by side, on the tibia of a skeletonized corpse, which was recovered from a forested area of Chiang Mai, northern Thailand. In the triangular shape of the anterior end of the puparia, three thoracic segments and broad hairy patches beginning dorsolaterally at the sixth segments were distinguishing characteristics. This study, showing pupariation of the flies along the bone of a corpse as well as morphological features, provides important guidance in identifying C. nigripes puparia. A key to differentiate puparia of C. nigripes from the other flies of forensic importance in Thailand is given. © 2005 Elsevier Ireland Ltd. All rights reserved.